Motivations and challenges faced by university students in pursuing entrepreneurship ventures: from UUM perspective - Umi Athirah Mohd Fauzi,; Sharima Ruwaida Abbas,; Rohani Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Extant definitions of entrepreneurship are variously related to opportunity pursuit, business creation, uncertainty, profit-seeking, and more, reflecting the myriad perspectives within and beyond the entrepreneurship field. This case study examined Universiti Utara Malaysia (UUM) students' motivations and challenges in pursuing entrepreneurship ventures. The study was motivated by understanding the motivations that drove students towards entrepreneurship and the challenges they encountered. The problem statements were to analyse the motivators that influenced UUM students to pursue entrepreneurial ventures and identify their challenges. The methodology of the quantitative method was used, adapting a sociological specimen of a Google form questionnaire that was distributed to 100 UUM students. Several questions regarding the topic were asked through the survey. The results and experimental outputs showed that UUM students were mostly motivated by self-employment and skills learned in lectures. However, they also faced various challenges, with lack of capital being the most significant barrier to starting their ventures. The study implied that UUM management now realised that students mostly face entrepreneurial motivators and challenges. Hence, the findings helped UUM policymakers design and implement tailored entrepreneurship programs that addressed the unique needs of students. By addressing these motivations and challenges, universities could better equip students to embark on successful entrepreneurial ventures, fostering innovation, economic growth, and job creation in the region.